Does Local Development Exist? Sustainability of Artisanal Agri-Industry of Jatropha Seeds in Yucatan - García, Armando Rucoba; Gil, Alfonso Munguía; López, María Isabel Cano (Asian Journal of Agriculture and Rural Development, 2013)
This study seeks to analyze the benefits, as well as the likely risks of cultivating Jatropha curcas in small production units of rain fed lands in Yucatán. In order to analyze the possible development of local artisanal agri-industry in the context of policies related to biofuels in Mexico, interviews with key informants were made to identify the agricultural potential of Jatropha c. in monoculture and associated crops. Its cultivation and using for biodiesel in the country will be possible as long as it not implies competition with crops for family consumption and it not represents an environmental degradation factor. Production of Jatropha c. on small areas could be a productive choice if public policies are established to promote biodiesel production and its use in national industry.